TRANSMISI NILAI PESSE’ SEBAGAI MODEL EMPATI DI SEKOLAH - Lebba Kadorre Pongsibanne (Sosio-Didaktika: Social Science Education Journal, 2014)
This article is motivated by the rise of violent behavior among students in Makassar, which raises concern for all parties. The purpose of writing this article is to provide an overview of the transmission pesse’ value ‘as a model of empathy in school. That the cultivation of the value of empathy is very important as one of the solutions to solve the problems associated with violent behavior among pupils and students. In this context, empathy is seen as something that is (becoming), not as something that is (being). Local wisdom of South Sulawesi has left Pesse’ as a model of empathy in school. The values pesse’ in schools as part of the development of character, should be viewed as a common framework that is constantly moving in synergy, both in terms of pattern and purpose in developing pesse’ value, to be used as an effective way to cut habitus violence already rooted among pupils and students in South Sulawesi.